Diagnosis of pancreatic cancer via1H NMR metabolomics of human plasma - Michálková, Lenka; Horník, Štěpán; Sýkora, Jan; Habartová, Lucie; Setnička, Vladimír (The Analyst, 2018)
Metabolic changes induced by pancreatic cancer were investigated by 1H NMR spectroscopy of plasma samples of patients and healthy controls. The acquired data were submitted to multivariate statistical analysis providing clear discrimination between both groups. The most significant differences were found in levels of 3-hydroxybutyrate and lactate. The obtained results (100% sensitivity, 90% specificity) clearly show the potential of 1H NMR spectroscopy in pancreatic cancer diagnosis. Therefore, the NMR-based metabolomics may contribute to the early diagnosis, prevention and/or therapy of diseases in the future. On the other hand, the number of samples in the presented pilot study is limited and has to be significantly increased in the future in order to obtain solid statistical models and to confirm the current findings.
Keywords: Female; multivariační analýza; ženské pohlaví; krev; Multivariate Analysis; Lactic Acid; Proton Magnetic Resonance Spectroscopy; kyselina mléčná; Pancreatic Neoplasms; lidé; Blood; nádory slinivky břišní; Metabolomics; Aged, 80 and over; metabolomika; Male; nádorové biomarkery; Aged; Biomarkers, Tumor; lidé středního věku; 3-Hydroxybutyric Acid; senioři nad 80 let; Amino Acids; senioři; mužské pohlaví; aminokyseliny; kyselina 3-hydroxymáselná; Middle Aged; protonová magnetická rezonanční spektroskopie; Humans